PEMBIASAAN MEMBACA AYAT ALKITAB SETIAP HARI BAGI MAHASISWA STT MAWAR SARON LAMPUNG DALAM MENGATASI DAMPAK NEGATIF ERA MEDIA SOSIAL - Telaumbanua, Isa Umbu Riani; Natanael, Yonatan; Zai, Yafarman (STT KINGDOM BALI, 2026)
The social media era poses serious challenges for theological students, including emotional instability, declining self-control, and value disorientation. This study aims to describe and analyze the role of daily Bible reading habits in addressing the negative impacts of social media among students of STT Mawar Saron Lampung. This research employs a descriptive qualitative method with in-depth interviews involving ten selected students who actively engage in daily Bible reading. Data were analyzed using thematic analysis to identify recurring patterns and meanings. The findings reveal that daily Bible reading functions as an emotional stabilizer, a medium for self-reflection and self-regulation, and a foundation for strengthening identity and life values in the digital era. This study fills a research gap by providing empirical qualitative evidence on spiritual habituation as a practical response to digital challenges within theological education. The results offer practical implications for spiritual formation programs in theological institutions.